Investigating the effect of ultrasonic waves on coagulants in dewatering of excess sludge of south of Tehran - farshad golbabei kootenaei; nasser mehrdadi; Gholamreza Nabi Bidhendi; hasan aminirad; Mahdi Asadi Ghalhari; Farima Saeedi (Mashhad University of Medical Sciences, 2019)
Abstract Background and purpose: Reducing the amount of sludge produced by the biological treatment of active sludge is of great importance. The main task of dewatering unit is to separate water from excess sludge. The aim of this study is to determine the effect of ultrasonic waves on coagulants in improving the sludge dewatering process and increasing solid content of sludge cake. Materials and methods:This is an experimental study performed in batch laboratory scale. During the two seasons, 12 samples were taken at 15 days' intervals. Variables include ultrasound density (0.375, 0.75, 1, 1.3 and 2.5) in watts per ml, Time (1, 5, 10, 15 and 30) in minute, and specific energy input (208, 1041, 2083, 3124 and 6249) in kilojoule on kilo total suspended solids. The effects of ultrasonic waves on coagulants were investigated by using Particle Size Analizer (PSA). Results:The optimum amount of solid content of sludge and capillary suction time (CST) was equal to 26.4 percent and 86 seconds in sonification time of 5 minutes and specific energy input of 1041 kj/kg TS. By applying ultrasonic waves, d10, d50, d90 and average particle size amount were equal to 6.3, 44.2, 24.4 and 28.84 micrometers respectively. Conclusion:Ultrasound waves create pores in the physical structure of the polymers and the increase of cationic surface charge increases the adsorption of particles and made larger flocs and can increase the solid content of sludge and improve sludge dewatering process.